Obesity-Related Glomerulopathy: From Mechanism to Therapeutic Target - Wei L (Dove Medical Press, 2021)
Lifang Wei,1,* Ye Li,2 Yue Yu,1 Minmin Xu,1 Huilan Chen,1 Lijie Li,1 Ting Peng,1 Kang Zhao,1 Yongze Zhuang3,* 1Department of Nephrology, The Third People’s Hospital Affiliated to Fujian University of Traditional Chinese Medicine, Fuzhou, Fujian, People’s Republic of China; 2The Third People’s Hospital Affiliated to Fujian University of Traditional Chinese Medicine, Fuzhou, Fujian, People’s Republic of China; 3Department of Nephrology, 900 Hospital of the Joint Logistics Team, PLA, Fujian University of Traditional Chinese Medicine, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lifang Wei; Yongze Zhuang Tel +86 591 62091295Fax +86 591 22869300Email liwlf2008@163.com; Doczhuang@aliyun.comAbstract: Obesity-related glomerulopathy (ORG) is a secondary glomerular disease caused by obesity, with clinical manifestations such as proteinuria and glomerulomegaly. Currently, the high incidence of obesity brings a change in the spectrum of kidney diseases across the globe, including China. ORG has become another important secondary nephropathy leading to end-stage renal disease (ESRD), and its incidence has increased significantly. This trend is bound to bring about a serious socioeconomic burden. Therefore, it is urgent to study its pathogenesis and intervention measures. Currently, the occurrence and development mechanisms in ORG are complicated by many factors, which are still unclear. In the past 20 years, with the continuous intensive research on mechanisms such as hypoxia in the metabolic process, immune inflammation, and pyroptosis, there have been new advances in the mechanism of ORG, especially the important role of inflammation in podocyte injury and its impact on the progress of ORG. Here, we briefly review the possible pathogenic role of the inflammasome in the podocyte damage in ORG and summarize the possible therapeutical strategies targeting inflammasome.Keywords: obesity, NLRP3 inflammasome, ORG, podocyte, Chinese herbal medicines